THE RETURNS OF VALUE AND GROWTH INVESTING IN THE FINNISH STOCK MARKET - Jussila, Sami (My University, 2012)
Value and growth investing are two of the most famous and widely known investment strategies. They are based on dividing stocks into value stocks and growth stocks. Value investing means investing in shares that have been priced to a low level with respect to some fundamental value of the share. Growth investing means investing in stocks that are priced to a high level with respect to the fundamental value of the stock. Based on numerous research papers value stocks are not riskier than growth stocks, but have still yielded better than growth stocks in the long run. The theory part of the study covers the most essential fields of financial theory regarding value and growth investing, such as pricing of securities and efficient financial markets. This study investigates whether a value premium has existed in the Finnish stock market over an investment horizon of 1.4.1999–31.3.2011. The E/P, B/P and the C/P ratios are used to determine value and growth. The second issue to be resolved is whether a value or a growth premium is caused by a greater amount of risk involved in the strategy. Furthermore, the sensitivity of the strategies to the starting point of the investment period is investigated. All of the three key ratios of this study proved to have a statistically significant effect on the associated stock returns. The values of the key ratios and the stock returns were positively correlated. By using a value strategy based on these key ratios it was possible to achieve superior risk-corrected returns in comparison to the returns of equivalent growth portfolios or the market index. The E/P ratio had the greatest effect on stock returns. However, the observed value premia or differences in the variances between corresponding value and growth portfolio returns were not proved to be statistically significant.
Keywords: value investing; growth investing; value premium; abnormal return; anomaly; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|